Analysis of the Implementation of National Education Standards in the Handicraft Training Program at PKBM Dahlia, Pekanbaru - Aulia Rahma Putri; Yuka Martlisda Anwika; Rahmat Fahmi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Nonformal education plays an important role in improving community skills and empowerment. One form of nonformal education is the handicraft training program organized by Community Learning Activity Centers (PKBM). This study aims to analyze the implementation of National Education Standards (SNP) in the handicraft training program at PKBM Dahlia. The research employed a descriptive approach using mixed methods. Data collection techniques were carried out through interviews, observations, and documentation involving administrators, tutors, and training participants. Data analysis was conducted descriptively using quantitative and qualitative approaches by relating the research findings to community education theories and nonformal education standards. The results of the study indicate that the implementation of the National Education Standards in the handicraft training program at PKBM Dahlia has been fairly effective, particularly in terms of the learning process, participant involvement, and the resulting skill outcomes. Participants were able to produce various handicraft products such as keychains, chenille wire flowers, and miniature ice cream stick models. However, several aspects still need improvement, especially in the learning evaluation system, monitoring the application of skills after training, and strengthening the economic impact for participants. Therefore, it is necessary to develop a more structured evaluation system, provide post-training assistance, and conduct entrepreneurship training to enhance the sustainability of the program.